PENGARUH KEPUASAN KERJA TERHADAP HASIL KINERJA DENGAN DIMEDIASI OLEH LOYALITAS KARYAWAN PERUSAHAAN PT. MUTIARA TIRTA DEWATA - Gede Sudipta Sana; Harry Widyantoro (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This purpose of the research is to analyze and identify the influence of job satisfaction on employee performance results for employees of the Company PT. Mutiara Tirta Dewata Surabaya uses employee loyalty as mediation. Research was conducted on employees of PT. Mutiara Tirta Dewata Surabaya with a total population of 80 people. The sample used was only 80 respondents because some samples did not match the criteria. The data collection technique used was a questionnaire using a conventional formula directly. Variable measurement uses a Likert scale with a scale of 1-5 and analysis for data processing uses the Structural Equation Model (SEM) method with the SMART PLS Ver application. 4.0.0. The research results show that job satisfaction has a positive effect on job performance, through the mediation of employee loyalty.